„FOR WHOM THE BELL TOLLS?” DEATH AND DYING-RELATED LANGUAGE/ VOCABULARY. LINGUISTIC BOUNDARIES IN ALBANIAN AND ROMANIAN - Dr. Benita STAVRE; Dr. Daniela STOICA; Dr. Erinda PAPA (Diversitate si Identitate Culturala in Europa)
Balkan languages entail many euphemisms regarding death and funeral rituals. This paper focuses on the comparative study of Romanian and Albanian euphemisms, emphasizing their often use in similar contexts and at the same time their semantic differences. The analyzed examples of Romanian and Albanian euphemisms are from everyday talk. The article will also include debates regarding the methods and context of using these euphemisms in the two languages, focusing on cultural and linguistic differences.